The Influence of Destination Image, Facilities and Promotion on the Decision to Visit the Mandalika Sport Tourism Area Through Motivation as a Mediating Variable - Maizati Maulidna; Didy Ika Supryadi (LP2M IAIN Palopo, 2026)
Mandalika sport tourism faces the challenge of optimizing destination image, facilities, and promotions for post-MotoGP event tourist visit decisions. This study examines the influence of these three factors through motivational mediation using a causal associative quantitative approach. The Mandalika tourist population was purposively sampled with 100 respondents via an online Likert questionnaire. SmartPLS PLS-SEM analysis confirmed the instrument's validity and reliability (AVE>0.50, CR>0.70). The results showed significant direct (β=0.197-0.474, p<0.05) and indirect effects through motivation (0.097-0.173), with a moderate R² (40.6-46.7%). Motivation proved to be the dominant mediator. The conclusion recommends a sustainable strategy for destination management.